The Effect of Shipping Value, Location and Service Quality on Consumer Satisfaction on JNE Goods Delivery Services in Medan Johor District, Medan City - Adhani, Nadia; Lubis, Irsad (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The purpose of study This is For know and analyze Influence of Shipping Value, Quality Service and Location to Satisfaction JNE Medan Johor Customers. Population in the study that is customer user JNE Medan Johor services. Samples used in study This as many as 80 people. Deep data collection techniques study This use technique question or questionnaire questionnaire. Data analysis techniques using analysis descriptive and analytical multiple linear regression. Data processing in study using SPSS 26. Based on results study in a way partial show that Shipping Value influential positive and significant to Satisfaction Customer, Quality Service influential positive and significant to Satisfaction Customers, and Location matters positive and significant to Satisfaction Customers, and in general simultaneous Shipping Value variables, Quality Service and Location matter in a way significant to Satisfaction JNE Medan Johor customers. And based on coefficient determination variable dependent capable influence variable dependent as much as 50.8%.